Aftermath of Terror: A Nationwide Longitudinal Study of Posttraumatic Stress and Worry Across the Decade Following the September 11, 2001 Terrorist Attacks. Issue 1 (7th March 2018) - Garfin, Dana Rose; Poulin, Michael J.; Blum, Scott; Silver, Roxane Cohen
Abstract: Research conducted in the early years after the September 11, 2001 (9/11) terrorist attacks in New York, Pennsylvania, and Washington, DC demonstrated adverse psychological outcomes among residents of the United States who were exposed to the attacks both directly and indirectly via the media. However, less is known about the impact of this collective trauma over time. Beginning at the end of December 2006, a longitudinal study of a nationally representative sample of U.S. residents (Cohort 2, N = 1, 613) examined the long‐term effects of 9/11, with annual assessments administered every year for 3 years. We assessed rates of 9/11‐related posttraumatic stress (PTS) annually during the first 2 years of the study; during the second and third years of the study, we assessed fear and worry regarding future terrorism. Rates of PTS among participants were compared with those assessed annually in a nationally representative sample between 2002 and 2004 (Cohort 1); results indicated a relatively stable pattern of 9/11‐related PTS symptoms for 6 years following the attacks. Five to six years after 9/11, we found an association between 9/11‐related PTS and both direct, B = 8.45, 95% CI [4.32, 12.59] and media‐based (live television), B = 1.78, 95% CI [0.90, 2.65] exposure to the attacks. Six to 7 years post‐9/11, fear and worry regarding future terrorism were predicted by 9/11‐related PTS symptoms that had been reported approximately 5 years after the attacks, B = 0.04, 95% CI [0.03, 0.05]. The psychological legacy of 9/11 was perceptible among many U.S. residents throughout the decade that followed.